Ascendancy of Solar Variability on Terrestrial Climate: A Review - A.K. Singh,; Asheesh Bhargawa, (Journal of Basic & Applied Sciences, 2020)
In the present paper, we have briefly reviewed the impact of solar activities on the terrestrial climate. Increased/decreased solar activity affects the various processes going on into the Sun-Earth system and alters the composition of parameters responsible for the climate change. The amount of high solar activity (sunspots) is directly related with the total solar irradiance (TSI) while the spectral index is associated with the ultraviolet (UV) radiations coming from the Sun. Contrary to the above, decreased solar activity is accountable for increased incidence of the galactic cosmic rays (GCR) which play significant role in cloud formation and ultimately responsible for the changed climate conditions of terrestrial environment. The influence of solar variability on the Earth's climate can be explained by exploring various mechanisms involved. There are no fool proof evidences that the solar variations are a major factor in driving recent global climate change but there are considerable evidences of solar influence on the climate of particular regions as well as throughout the terrestrial environment. During high solar activity, higher temperatures and larger ozone concentrations are observed in the tropical stratosphere. The solar influences on the Earth’s climate mainly includes; the changed occurred due to variations in the Sun's radiant output (TSI and UV) and the changes occurred due to the Sun's influence on the energetic particles reaching to the Earth (Solar Energetic Particles, Galactic Cosmic Rays).Following the above regime, we have provided the evidences for the existence of physical links between solar activity and terrestrial climate. Summary of our present understanding of the mechanisms involved in the Sun-climate dynamics are presented